The Popular University in Brazil - José Eustáquio Romão; Adriana Salete Loss (FahrenHouse, 2014)
This article focuses on the Brazilian university crisis and its alternative for change and innovation, at the curricula and at the institutional level. It points out the university capacity to take into account critical contexts, developing political and epistemological actions in order to struggle with social problems. In its struggle, university is shown as responsible of the solutions of humans are exposed by their social and political contexts. Brazilian university has gotten the legacy from European corporative model and also from American technocratic idiosyncrasy. The Southern Frontier Federal University (UFFS) is one of the new federal universities created by the government into the National Program for Education (2000-2010) in order to extend the range of access to public higher education along the country. Thus, this university tries to solve some of the historical educational problems of Brazilian education. This article discusses this project and points out some insight regarding this topic. Received: 11/08/2013 / Accepted: 30/10/2013 How to reference this article Romão, J. E., Loss, A. S. (2014). A Universidade Popular no Brasil. Foro de Educación, 12(16), pp. 141-168. doi: http://dx.doi.org/10.14516/fde.2014.012.016.006